Increasing patient participation in hand hygiene practices in adult surgical wards in a tertiary institution: a best practice implementation project. Issue 1 (6th March 2022) - Choong, Tze Lin; Lim, Zhao Jun; Ho, Alexander Guan Ting; Goh, Mien Li
ABSTRACT: Introduction: The WHO states that hospital-acquired infections may be transmitted through contaminated hands. Practicing hand hygiene using alcohol-based handrub or soap and water reduces harmful organisms. The Joanna Briggs Institute (JBI) best practice recommends empowering patients with hand hygiene knowledge and engaging their involvement to strengthen hand hygiene practices. Aims: The aim of this project was to improve hand hygiene among surgical inpatients. Methods: This evidence-based quality improvement project was conducted in three phases: the baseline audit, implementing best practice, and the postimplementation audit. Participants were patients hospitalized in three surgical wards of a 1200-bed acute care tertiary hospital. This project utilized the online JBI Practical Application of Clinical Evidence System and The Getting Research into Practice program to identify barriers and strategies. Nurses provided patients with an education pamphlet and regularly reminded them to improve their hand hygiene practices. Results: Ninety-four patients were audited between April and June 2018. Patients' hand hygiene practices improved from 19.1% at baseline audit to 61.7% ( P < 0.01) at first follow-up audit. Patients' hand hygiene improved from 48.9 to 72.3% ( P = 0.03) before meals, and from 92.6 to 98.9% ( P = 0.65) after toileting. The proportion of patients who received a hand hygiene information leaflet in an appropriate language increased from 64.9 to 89.4% ( P < 0.01). Conclusion: Patients' involvement in the hand hygiene program has significantly improved their hand hygiene practices. Patient education and patient information leaflet continue to be an effective strategy to improve knowledge and practices.